Analyzing the design of montessori-based media to introduce letters and numbers - Dandi Yunidar; Nurul Fitriana Bahri; Ica Ramawisari; Sheila Andita Putri (Universitas Indraprasta PGRI, 2025)
This research analyzes the design aspects of Montessori-based educational tools, such as sandpaper letters, sandpaper numbers, and moving alphabet; employed in early childhood education to introduce letters and numbers. The study aims to evaluate functionality, safety, usability, aesthetic appeal, construction quality, developmental impact, and compliance with standards. Utilizing qualitative analysis and interviews with educators and parents, the data were analyzed using thematic analysis, where interview transcriptions were coded and grouped into categories to identify key themes. The interviews were semi-structured, allowing flexibility for respondents to share their perspectives and experiences in depth. The research examines these tools' effectiveness in facilitating learning among young children. Results reveal varying levels of functionality, safety, and usability across the tools. Sandpaper letters and numbers offer moderate functionality and safety, emphasizing tactile learning, while moving alphabet presents higher functionality and interactive engagement. Usability is limited in static tools but heightened in the interactive moving alphabet. Aesthetic appeal varies, with all media focusing on engaging visual and tactile elements. Compliance with standards remains partial. The research underscores the significance of diverse design approaches in early childhood education and recommends iterative enhancements in usability, safety, and compliance for optimized learning experiences. These findings have implications for educators, suggesting the integration of interactive elements to bolster early childhood education's efficacy.